Case studies in environmental management in Central and Eastern Europe (Sheffield, 1999)
"As Central and Eastern European countries queue up to become members of a widely expanded European Union, the question of how their environmental laws and performance can become consistent with current standards has become of paramount importance. Forecasts are largely gloomy, with some commentators suggesting that it will take decades for full ... more »compliance to be achieved. This casebook presents the experiences of 14 companies in integrating environmental considerations in day-to-day operations in these emerging economies. The companies, both large and small, represent different sectors in the Czech Republic, Estonia, Hungary, Latvia, Lithuania and Poland. The book presents best-practice examples from companies that have successfully integrated environmental concerns into business management and improved their environmental as well as economic performance as a result. They show that different types of change are needed: technical, organizational and behavioural, and that only companies that embrace change can be successful in the big picture that is opening up for these countries. The work is presented in a graphic format with country, sector and company overviews, maps, tables, figures and photographs."